Abundance of Phytoplankton In The Coastal Waters of South Sumatera - Riris Aryawati; Dietriech G. Bengen; Tri Prartono; Hilda Zulkifli (Marine Science Department Diponegoro University, 2017)
Phytoplankton in the ocean has an important role in forming the base of food chain, responsible in primary production. Its abundance and number of phytoplankton species will indirectly affect the level of water’s fertility. This study aimed to determine the presence of phytoplankton as bio-indicators of water quality in terms of abundance, diversity index, uniformity index, and saprobic coefficient in coastal waters of South Sumatera. The study was conducted on May 2013 - February 2014, at ten stations during high and low tides. Phytoplankton samples were taken vertically using plankton nets, cone-shaped with a diameter of 30 cm, length 100 cm and mesh size 30 μm. The study found 41 genera of phytoplankton, consisted of family Bacillariophyceae (26 genera), Dinophyceae (7 genera) Cyanophyceae (7 genera) and Chlorophyceae (1 genus). The highest number of genera was recorded while low tides in November (24 genera), and the lowest was on May while high tides (16 genera). The highest abundance of phytoplankton was recorded in August during high tides (2,68 x 107 cell.m-3), and the lowest was in May during high tides (6,59 x 105cell.m-3). The diversity index (H'), the uniformity index (E), and the dominance index (D) ranged between 0,64–3; 0,15–0,71 and 0,15–0,83 respectively. Keywords: phytoplankton, abundance, diversity index, South Sumatera coast.